IS THERE REALLY A NEED TO CREATE «REGIONAL PERCENTILE CURVES» OF WEIGHT-HEIGHT PARAMETERS? (COMMENT TO THE ARTICLE BY RITA R. KILDIYAROVA «ASSESSING PHYSICAL DEVELOPMENT OF CHILDREN WITH PERCENTILE DIAGRAMS») - Svetlana G. Makarova (Вопросы современной педиатрии)
Height, body weight and body mass index are important parameters of health and are widely used in clinical practice, for assessing health of children, and for population studies. Amid the general globalization, the main trend of the present time is joining efforts of various countries for prevention and treatment of diseases in children. The work of the World Health Organization (WHO) on creation of international standards of anthropometric measures and parameters of children's development is based upon this trend. A key point of the WHO standards is their creation based on a survey of a large cohort of children (from 5 countries of 6 continents) who were in optimal conditions: who were breast-fed and received the up-to-date level of care and quality of the provided medical care. This actually allowed to eliminate the main exogenous factors that affect such parameters and to make them, in fact, the reference ones. The application of a unified approach using the WHO standards allows to carry out multicenter studies involving different countries as well as to compare the data obtained in different regions. Studies have shown that the WHO standards for physical development are applicable in different regions of the world. In this regard, the creation of «regional» reference curves for height and body weight of children that are different from the generally accepted standards is currently inappropriate, but it is really relevant to use the WHO standards.